Dense GeV electron–positron pairs generated by lasers in near-critical-density plasmas - Xing-Long Zhu (Nature Portfolio, 2016)
High power lasers can produce electron-positron pairs at GeV energies, but doing so through laser–laser collisions would require exceedingly high intensities. Here the authors present an all-optical scheme for pair production by irradiating near-critical-density plasmas with two counter-propagating lasers.